2017
DOI: 10.12659/msm.902528
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Investigation of High-Intensity Focused Ultrasound (HIFU) Hat-Type Ablation Mode

Abstract: BackgroundThe aim of this study was to investigate the feasibility of the application of high-intensity focused ultrasound (HIFU) hat-type ablation mode in in vitro and in vivo models, and to compare the ablation effects of different parameter combinations.Material/MethodsHIFU hat-type ablation was performed in isolated bovine liver tissue and in the liver tissue in living rabbits, and the coagulative necrosis for different parameter combinations (plane angles and irradiation order) was investigated. We also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies have shown that blood flow in vessels feeding the target tissue can disperse US energy and affect heat deposition . For PHIFU at a lower DC to achieve the same effective irradiation time as CHIFU, an increase in the total irradiation time is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that blood flow in vessels feeding the target tissue can disperse US energy and affect heat deposition . For PHIFU at a lower DC to achieve the same effective irradiation time as CHIFU, an increase in the total irradiation time is required.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of methods for improving the HIFU ablation efficiency have been proposed, including the use of special ablation patterns, vascular embolization, iodide oil injections, microbubble contrast agents, and other materials with acoustic impedance. Although these methods have achieved some beneficial results, they also have certain limitations or side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] MRgFUS is most commonly used to ablate brain tissue in a targeted fashion. 5 The FDA cleared MRgFUS for ablation of the ventralis intermediate nucleus of the thalamus to treat essential tremor in 2016 6 and, more recently, for the globus pallidus interna for treatment of advanced Parkinson disease. 7 Currently, the FDA-cleared system for transcranial MRgFUS is the ExAblate Neuro system (Insightec).…”
mentioning
confidence: 99%